The Role of Trust: Teacher Capacity During School Leadership Transition - Hong, Ji; Cross Francis, Dionne; Wang, Qian; Lewis, Laura; Parsons, Alexandra; Neill, Crystal; Meek, Diana (Frontiers in Education, 2020)
The purpose of this research is to examine teachers’ capacities and the role trust plays in the professional lives of teachers during the transition to a new team of three administrators in an elementary school located in a low-income urban community in the U.S. Twenty-seven teachers’ surveys and interviews showed that the transition caused some level of instability and uncertainty; however, teachers had a positive sense of efficacy, social capital, resilience, and emotions. The four themes emerged from the interviews – common goals and vision for students, beliefs in colleagues’ competence, emotional safety and comfort, and being vulnerable with colleagues -- appear to function as conditions to build trust among colleagues. The trusting relationships seem to help teachers withstand the challenging transition by providing a safe space where teachers can learn and grow. Implications for school administrators and district offices were discussed.